White rabbit - Roehrig, Caleb (Feiwel and Friends, 2018)
Rufus Holt has one night to prove his half-sister, April, innocent of murdering her boyfriend at a wild party--the very night his ex-boyfriend, Sebastian, shows up wanting to talk.